Characterization and evolution of the coronavirus porcine epidemic diarrhoea virus HLJBY isolated in China. Issue 1 (22nd August 2019) - Huan, Changchao; Pan, Haochun; Fu, Siyao; Xu, Weiyin; Gao, Qingqing; Wang, Xiaobo; Gao, Song; Chen, Changhai; Liu, Xiufan
Abstract: A strain of porcine epidemic diarrhoea virus (PEDV), namely HLJBY, was isolated in Heilongjiang province, China. To provide insight into the understanding of the phylogenetic and the current epidemiological status of PEDV, PEDV HLJBY was compared with CV777 and other PEDV strains deposited in the GenBank. The homology between the entire genomic nucleotide sequences of PEDV HLJBY and CV777 was 97.7%. The homology of M gene was the highest (99.0%). However, the homology of ORF3 gene was 97.7%, and protein of ORF3 was 90.1%. In addition, HLJBY showed the highest nucleotide identity (99.9%) with PEDV‐SX/China/2017 strain and lowest similarity (91.2%) to PEDV/Belgorod/dom/2008 strain. We analysed the changes in S gene and its protein of PEDV HLJBY with 65 historic PEDV strains. The highest nucleotide identity was 99.9% compared with PEDV‐SX/China/2017 strain, and the lowest nucleotide identity was 60.0% compared with PEDV/Belgorod/dom/2008 strain. The length of deduced amino acid sequences of S proteins varied from 1, 372 to 1, 390 amino acids (aa). Compared with most aa sequences of S proteins, HLJBY exhibited 5 aa deletions (position 55, 59–61, 144). Analysis and comparison of open reading frame 3 (ORF3) proteins between HLJBY strain and other PEDV strains were also focused in this study. We revealed that the length of deduced amino acid sequences of ORF3 proteins was 80–224 aa among tested strains and the identity of HLJBY ORF3 amino acids with other PEDV strains was 71.4%–98.9%. ORF3 protein of both HLJBY strain and PEDV‐SX/China/2017 strain consists of 91 aa, with 133 aa deletions at their C' end in relation to the other tested PEDV strains. The phylogenetic tree based on different proteins or genes resulted in different phylogenetic groups. For pathogenicity evaluation of PEDV HLJBY strain, colostrum deprivation piglets were challenged with PEDV HLJBY, and PEDV reference strain CV777 as a control, the results showed that animals challenged with either of these PEDV strains developed diarrhoea, and histopathological examination of small intestines of challenged animals showed acute viral enteritis with villous atrophy in either PEDV HLJBY‐P10 or PEDV CV777‐P8 inoculated piglets.